Effect Of Corona Virus Disease 2019 (Covid-19) on the Incidence of Preterm Birth And Asphyxia at Banjar Regional General Hospital - Kulfa Sholehah; Akhmad Yogi Pramatirta; Firman F. Wirakusumah (Indonesian Journal of Obstetrics & Gynecology Science, 2023)
Objective: This study aims to determine and analyze the effect of Corona Virus Disease (Covid-19) on the incidence of preterm birth and asphyxia at Banjar Regional General Hospital. Method: This was an analytical observational study with a retrospective cohort approach. The type of data involved in this study was secondary data derived from medical record with a total sample of 59 women in labor diagnosed with Covid-19 and 513 women in labor who were not diagnosed with Covid-19.Results : The result of the study showed that there was a significant difference in the incidence of preterm birth between women in labor diagnosed with Covid-19 and those who were not diagnosed with Covid-19 (ρ value=0.000 or ρ<0.05). Regarding the incidence of asphyxia, the result showed that there was no difference in the incidence of asphyxia between infants born to women diagnosed with Covid-19 and those born to women who were not diagnosed with Covid-19, with a ρ value of 0.523 or ρ>0.05. Women diagnosed with Covid-19 were at risk of giving birth to premature infants 5.308 times compared to women not diagnosed with Covid-19. The OR of the incidence of preterm birth was 5.308 with a 95% CI of 3.035-9.281. Furthermore, based on the statistical test result, it was revealed that Covid-19 had a low effect on the incidence of asphyxia with the OR value of 0.839 and a 95% CI of 0.489-1.439.Conclusion: Based on the results of the study, it can be concluded that there was an effect of Covid-19 just on the incidence of preterm birth.Pengaruh Corona Virus Disease 2019 (Covid-19) terhadap Kejadian Prematur dan Asfiksia di RSUD Kota BanjarAbstrak Tujuan: Penelitian ini mengukur dan menganalisis pengaruh Corona Virus Disease (Covid-19) terhadap kejadian prematur dan asfiksia di RSUD Kota Banjar. Metode: Penelitian berupa analitik observasi dengan pendekatan kohor retrospektif. Jenis data dalam penelitian ini adalah data sekunder dari rekam medis dengan jumlah sampel menggunakan total sampel yaitu 59 ibu bersalin dengan Covid-19 dan 513 ibu bersalin tidak dengan Covid-19.Hasil: Hasil penelitian menunjukkan terdapat perbedaan yang bermakna kejadian prematur pada Ibu Covid-19 dengan ibu yang tidak terdiagnosis Covid-19 (nilai ρ0.000) yang artinya p0.05. Ibu dengan Covid-19 berisiko melahirkan bayi prematur 5.308 kali dibandingkan pada ibu yang tidak terdiagnosis Covid-19, nilai OR kejadian prematur 5.308 dengan IK 95% 3.035-9.281. Dan dari hasil uji statistik diperoleh hasil yaitu Covid-19 berpengaruh rendah terhadap kejadian asfiksia dengan hasil uji statistik nilai OR 0.839 dengan IK 95% 0.489-1.439. Kesimpulan: Dari hasil penelitian dapat disimpulkan bahwa terdapat pengaruh Covid-19 terhadap kejadian prematur.Kata kunci: Asfiksia, Covid-19, Prematur